SISTEM PENGAMBLAN KEPUTUSAN PEMILIHAN BIBIT JAGUNG DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA TOKO ABADI JAYA LAMPUNG TIMUR - Ferly Ardhy; Supriyanto Supriyanto; Afif Zakhulan (Jurnal informasi dan komputer, 2018)
AbstracCorn Seed is a very popular commodity crop planted by farmers especially Indonesia because many who use this plant besides many benefits it is also a panga plant. Users usually have difficulty choosing corn seeds that they want to buy because of the many types of corn seeds, soil construction, and prices. So that a decision support system is needed that can help users determine Corn Seed according to the alternatives and desired criteriaIn this study, the method used is the Analitycal Hierarchy Process (AHP), System development methods are made using the Prototyping method using a Unified Modeling Language (UML) system development tool consisting of Use Case, Activity Diagram, Sequence Diagram, and Class Diagram and using the PHP programming language and using the MySql database.This method is used because it is able to choose the best alternative so as to produce optimal decisions in accordance with the specifications and funds owned by the user.